Simple and practical method of characterizing the parametric down-conversion source - 王东;伍娟;赵良圆;安雪碧;银振强;陈巍;韩正甫;王琴 (Chinese physics B, 2017)
Parametric down-conversion（PDC） sources play an important role in quantum information processing, therefore characterizing their properties is necessary. Here we present a statistical model to assess the properties of the PDC source with certain distribution, such as the brightness and photon channel transmissions, we only need to measure the singles and coincidences counts in a few seconds. Furthermore, we validate the model by applying it to a PDC source generating highly non-degenerate photon pairs. The results of the experiment indicate that our method is more simple, efficient, and less time consuming.